Application of Wireless Communication Technology in High-speed Train Network Control Systems - WANG Huawei; GAO Yang; LI Hailong; ZHANG Ziqi; LIU Cong; DONG Weijin (Chengshi guidao jiaotong yanjiu)
［Objective］ Wireless communication technology, known for its high flexibility and strong adaptability, can effectively address many issues associated with wired networks in the high-speed train operational environment. However, due to the complex nature of this environment, the application of wireless communication technology in this field still faces numerous challenges that require in-depth researches. ［Method］ The hardware system used in the tests is introduced, detailing the composition of the NDT (network delay tester) and the specific specifications of the bridge devices under test. Three simulated environmental conditions are set up: Condition 1 (corridor environment), Condition 2 (close to the ground), and Condition 3 (blocked by an iron door). Testing software is used to obtain data on signal throughput and one-way transmission delay of wireless communication under the three conditions. The tested data are analyzed to identify the propagation characteristics of wireless signals and potential interference factors under the three conditions. ［Result & Conclusion］ The three conditions all have varying degrees of impact on signal throughput and transmission delay of wireless transmission. Metal substances between train compartments exhibit a significant shielding effect on radio waves. The wireless signal performs best under Condition 1, followed by Condition 2, with Condition 3 showing the worst performance.